TEKNIK HUMOR ARTHUR ASA BERGER SEBAGAI MEDIA KRITIK SOSIAL PADA TAYANGAN LAPOR PAK! TRANS7 - Indriani, Rizki; Irfai Fathurohman; Ahmad Hariyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes humor techniques as an instrument of social criticism in the Lapor Pak! Trans7 through the lens of Arthur Asa Berger's theory. Using a qualitative descriptive approach, primary data was sourced from the speech in the episode